Bacteriolysis by vancomycin-conjugated acryl nanoparticles and morphological component analysis. (June 2014) - Shimizu, Naoto; Otsuka, Kazuhito; Sawada, Hajime; Maejima, Tatsuo; Shirotake, Shoichi
Abstract Nanoparticles are currently attracting considerable attention because of their ability to conjugate to various substances. As such, these nanoparticles can assist the transfer of the conjugated substance to target tissues where they are gradually released. In this study, vancomycin-conjugated nanoparticles (VCM NPs) were prepared. The antibacterial activity of VCM NPs was compared with that of VCM alone by exposure to vancomycin-resistant enterococci (VRE). The morphology of the cells was then analyzed by electron microscopy. VCM NPs were found to have more potent antibacterial activity against VRE compared to VCM alone, but the activity against vancomycin-sensitive enterococci (VSE) remained the same. The antibacterial activity of nanoparticles alone was the same against VSE and VRE. The nanoparticles were found to induce characteristic morphological changes in the bacteria based on scanning and transmission electron microscopy. The results suggest that the strong antibacterial activity of VCM NPs against VRE may be attributable not only to the well-known control release carrier property of the nanoparticles but to an additional mechanism that involves VCM NPs avoiding the drug resistant mechanism of VRE.